Efeitos do Sulforafano sobre a disfunção cognitiva induzida pelo acúmulo de ferro cerebral - Lavich, Isabela Cavalheiro (2015)
Iron is essential in the neonatal brain for normal neurological development and for establishment of the concentration of iron in the adult brain, as iron absorption is greatest during the neonatal period. It is believed that iron overload contributes to the development of neurodegeneration, the exacerbation of the normal apoptosis rates, largely due to its participation in the Fenton reaction and production of reactive oxygen species. Previous studies in our laboratory have shown that treatment with iron in the neonatal period worsens the memory, as well as an increase in oxidative stress parameters and levels of apoptotic proteins. Recently, we have also demonstrated that this treatment reduces synaptophysin levels (a synaptic marker) in the rats hippocampus. Mitochondria are involved in this process because they are considered the main intracellular source of superoxide anion and the main target of attack by free radicals. They are highly dynamic organelles that bind (fusion) and divide (fission) in response to environmental stimuli, developmental status and energy needs of the cells. Mitochondria are widely distributed in all neurons, but mitochondria subpopulations are enriched pre-synaptically in nerve terminals and post-synaptically in dendrites. In addition, they have been implicated in the pathogenesis of a wide variety of neurodegenerative diseases where synapses are known to be the main target. Sulforaphane is a natural compound that has been studied since the 1980s and considered to possess antioxidant and anti-inflammatory properties. This study aims to investigate the effects of treatment with Sulforaphane in adulthood on memory deficits and changes in markers of mitochondrial function, DNML1 and OPA1, and synaptic marker synaptophysin induced by neonatal iron treatment. Male Wistar rats received, orally, vehicle or carbonyl iron (30mg / kg) from the 12th to the 14th postnatal day. In order to evaluate the effects of acute Sulforaphane treatment on memory, rats were trained in the object recognition task and received one single intraperitoneal injection of Vehicle or Sulforaphane (0.5 or 5 mk/kg) immediately after training. To evaluate the effects of Sulforaphane chronic treatment on memory, rats received vehicle or Sulforaphane (0.5 or 5 mg / kg) for 14 days every other day, and were trained in the object recognition task 24 h after the last injection. The memory analysis was performed using the recognition index, expressed as the ratio between the amount of time spent in exploring the new object on the total time spent exploring both objects. DNML1, OPA1, and synaptophysin levels in the hippocampus were quantified by Western blotting. The quantification of protein was performed by measuring the density of the individual bands, normalized by β-actin density. Data were analyzed by comparing the averages for analysis of variance (ANOVA), with p <0.05 considered statistically significant. Our results showed that acute treatment with Sulforaphane (0.5 mg / kg) did not improve memory but at a dose of 5 mg / kg it was able to restore the memory deficits induced by iron. Chronic treatment with Sulforaphane, at both doses, also recovers the memory in rats treated with iron in the neonatal period. Sulforaphane at the dose of 5 mg/kg also recovers DNM1L mitochondrial alteration and synaptophysin in the hippocampus, confirming a possible neuroprotective role for this compound.